The Role and Characteristics of Educators in Islamic Education: - - Titania Rahima; Tsabitah Khairun Nisa; Muhammad Fiqri Aditya (Jurnal Pendidikan Islam, 2024)
Educators in PAI have a very crucial role. Educators must be good role models for students by showing behaviors that reflect Islamic teachings such as honesty, patience, and caring. The purpose of this study is to explore the roles and characteristics of educators in Islamic education. This study used a descriptive qualitative approach to examine the role and characteristics of educators in PAI. Data were collected and analyzed from various sources such as books and journals, focusing on literature and descriptive analysis. The results showed that effective PAI educators have a deep love for Islam, an empathetic attitude, and a deep understanding of student development. They are able to create a conducive learning environment, inspire students to delve deeper into Islamic teachings, and develop critical thinking, communication, and cooperation skills that are essential for students' future. By understanding these factors, it is hoped that effective solutions can be found to improve the quality of Islamic religious education in schools.